Yaroslav Prymachenko. Development of transport services in Kyiv in the early 20th century in the newspaper "Kievlyanin" : Yaroslav Prymachenko. Development of transport services in Kyiv in the early twentieth century in the newspaper «Kievlyanin» - Prymachenko, Yaroslav (Young Scholars Grinchenko – Seton International Journal, 2022)
Yaroslav Prymachenko. Development of transport services in Kyiv in the early 20th century in the newspaper "Kievlyanin"